Розробка компонентів інформаційної системи онлайн кінотеатру - Дідусь, О. П. (ХНУРЕ, 2024)
The work discusses the current stage of the development of the field of entertainment, in which information technologies and software tools currently play an important role. Currently, the situation is such that technical progress provides more and more opportunities for automation of certain services in any spheres, including the sphere of entertainment. Most of the content consumed by people is online. Therefore, the online cinema solves most of the shortcomings of the physical one. There are many films and screenings for their viewing, and there are also many who want to watch this or that novelty, so it is much easier not to waste your time on the way to the cinema, time in queues, not to mention the clear schedule of cinemas and the meaning of viewing.
Keywords: інформаційна система; онлайн кінотеатр